The Relationship Between Financial Development and Economic Growth in The United Kingdom: A Granger Causality Approach - Samuel Wesiah; Sixtus Cyprian Onyekwere (Yayasan Ahmar Cendekia Indonesia, 2021)
This study aims to investigate the causal relationship between financial development and economic growth in the UK using quarterly data from 1963q1 to 2015q1. Three variables were used as proxies for financial sector development, namely, ratios of broad money supply to GDP, ratios of private sector credit to GDP and the ratios of stock market capitalization to GDP. Economic growth was measured using real GDP per capita. In order to achieve stated aim, the study employed the Johansen Cointegration test and the Granger causality test within a vector error correction framework (VEC) to test for the existence (or not) of a long run relationship as well as the direction of causality between financial development and economic growth. The result from the Cointegration test indicates that there is a stable long run equilibrium relationship between financial development and economic growth in the UK. The Granger causality test presents evidence of a bidirectional causality. This suggests that financial development and economic growth are mutually causal, that is, causality runs from both side which is in line with the feedback hypothesis in the literature which argue that financial development and economic growth exhibits a two-way causal relationship. In terms of each individual variable, the study finds that while bank credit to the private sector and stock market capitalisation Granger cause GDP per capita, GDP per capita on the other hand, Granger causes broad money supply.